High‐throughput ion exchange purification of positively charged recombinant protein in the presence of negatively charged dextran sulfate. (30th January 2014) - Markely, Lam Raga A.; Kurt, Lutfiye; Lau, Janet; Mane, Sarthak; Guan, Bing; Ryll, Thomas; Estes, Scott; Prajapati, Shashi; Bakhshayeshi, Meisam; Pieracci, John
<x xml:space="preserve">Abstract</x> Product quality analyses are critical for developing cell line and bioprocess producing therapeutic proteins with desired critical product quality attributes. To facilitate these analyses, a high‐throughput small‐scale protein purification (SSP) is required to quickly purify many samples in parallel. Here we develop an SSP using ion exchange resins to purify a positively charged recombinant growth factor P1 in the presence of negatively charged dextran sulfate supplemented to improve the cell culture performance. The major challenge in this work is that the strong ionic interaction between P1 and dextran sulfate disrupts interaction between P1 and chromatography resins. To solve this problem, we develop a two‐step SSP using Q Sepharose Fast Flow (QFF) and SP Sepharose XL (SPXL) resins to purify P1. The overall yield of this two‐step SSP is 78%. Moreover, the SSP does not affect the critical product quality attributes. The SSP was critical for developing the cell line and process producing P1. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:516–520, 2014